Flow coefficient of the aggregates as a parameter characterizing the suitability of non-cohesive soils for earthworks - Majer, Stanisław (Scientific Review Engineering and Environmental Sciences (SREES), 2020)
The article presents the results of the flow coefficient of aggregate for 30 sands and aggregates. The introduction of European standards for the assessment of construction aggregates over 20 years ago introduced a number of new testing methods not previously used in Poland. One of them is the flow coefficient of aggregate, popularly called aggregate angularity. The method of determination is given in the standard PN-EN 933-6:2014. This standard defines the method of determining the index for coarse aggregates with grain sizes between 4 and 20 mm and fine aggregates with grain sizes below 2 mm. This test is particularly important when designing mineral-asphalt mixtures. Aggregate angularity, particularly in fine aggregates, is the main factor influencing the workability of mixtures. The flow time through the apparatus depends on the degree of roundness and form of the grain. The study determined the relationship between the flow coefficient of aggregate and CBR in relation to the uniformity coefficient. This indicator is still considered to be one of the main parameters that affect the suitability of non-cohesive soils in earthworks. It was proven that Ecs is more dependent on CBR than CU.